An assessment of the knowledge, attitudes and practices of caregivers of HIV positive children on treatment in Pretoria, South Africa : a cast study of out-patients in Kalafong hospital, Pretoria - Ofunne, Ifeanyichukwu (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.